1987
DOI: 10.1210/jcem-65-2-282
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal Androgen Response to Metyrapone, Adrenocorticotropin, and Corticotropin-Releasing Hormone Stimulation in Children with Hypopituitarism*

Abstract: We determined the adrenal steroid responses to metyrapone, ACTH, and CRH in 12 ACTH-intact and 5 ACTH-deficient hypopituitary children to determine the mechanisms that control adrenal androgen secretion. Serum adrenal androgen concentrations [dehydroepiandrosterone (DHEA) and delta 4-androstenedione (delta 4-A)] rose in response to oral administration of metyrapone (450 mg/m2 X dose, every h for 7 doses) in ACTH-intact hypopituitary children with multiple or isolated pituitary hormone deficiencies [mean postma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…In many peripheral steroid tissues such as the prostate and mammary glands, DHEA can be converted into androgens and/or estrogens (45), which also have immunomodulatory functions. However, a role independent of its metabolic functions and, in particular, on immune regulation has been previously observed (31,46). For example, DHEA was shown to have immunomodulatory properties in androgen-unresponsive mice (47).…”
Section: Discussionmentioning
confidence: 96%
“…In many peripheral steroid tissues such as the prostate and mammary glands, DHEA can be converted into androgens and/or estrogens (45), which also have immunomodulatory functions. However, a role independent of its metabolic functions and, in particular, on immune regulation has been previously observed (31,46). For example, DHEA was shown to have immunomodulatory properties in androgen-unresponsive mice (47).…”
Section: Discussionmentioning
confidence: 96%
“…This steroid is produced by the adrenals in response to stimulation by ACTH [23], and is uniquely sulfated by an adrenal sulfotransferase to DHEAS in humans (and to a lesser extent in rodents) prior to export into the plasma [24]. DHEAS represents the major secretory product of the human adrenal gland [28], and exhibits interesting and characteristic plasma levels throughout an individual's life-span.…”
Section: Discussionmentioning
confidence: 99%
“…production and secretion of the weak androgen steroid DHEA [23]. This knowledge, coupled to our present understanding about the molecular mechanisms that have been proposed to explain the transcriptional enhancing and transcriptional repressing influences of steroid hormones on steroid responsive genes [13-171, led us to question whether DHEA andor DHEAS could influence the ability of lymphocytes to produce TCGF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both low [1][2][3][4] and normal [5][6][7][8][9] levels have been reported. Of particular interest is the study of Cohen et al [2] which demonstrated markedly reduced plasma concentrations of the AA dehydroepiandrosterone (DHEA), DHEA sulfate (DHEA-S) and A4-androstenedione (A4A) in adolescent subjects with GH deficiency.…”
mentioning
confidence: 99%